Implementation of Spiritual Intelligence Values of Students In MAN All of Medan City - Juniati Harahap; Wahyudin Nur Nasution; Afrahul Fadhila Daulai (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to describe the implementation of students' spiritual intelligence values in MAN throughout Medan City. This research method is a qualitative research method with a phenomenological research approach. Data collection techniques using the method of observation, interviews, and documentation. Data analysis techniques, including data reduction, data presentation, and drawing conclusions. The results of this study consist of 3 components, namely 1) Students' spiritual intelligence includes the form of noble character, patience, sincerity to do everything and can solve all the problems that exist in their lives. The spiritual intelligence program for students at MAN throughout Medan City has the aim of assisting students in understanding and developing spiritual aspects, internalizing spiritual values, bringing students closer to religious teachings, and forming better personalities; 2) The values of spiritual intelligence depart from the principles through understanding and performing prayers well, one can develop spiritual awareness and experience closeness to Allah. Teachers emphasize the importance of building self-confidence, ethics, morals, morals, spiritual awareness, responsibility and fear of Allah SWT; 3) Implementation of students' spiritual intelligence values through efforts to internalize these values in positive actions and attitudes. This change was more visible in students majoring in religion, while the changes in students from other majors were minimal (low).